Evidence that cyanobacterial Sll1217 functions analogously to PGRL1 in enhancing PGR5-dependent cyclic electron flow - Dann, Marcel (Nat Commun, 2019)
In plants and cyanobacteria, the PGR5 protein contributes to cyclic electron flow around photosystem I. In plants, PGR5 interacts with PGRL1 during cyclic electron flow, but cyanobacteria appear to lack PGRL1 proteins. We have heterologously expressed the PGR5 and PGRL1 proteins from the plant Arabidopsis in various genetic backgrounds in the cyanobacterium Synechocystis. Our results show that plant PGR5 suffices to re-establish cyanobacterial cyclic electron flow (CEF), albeit less efficiently than the cyanobacterial PGR5 or the plant PGR5 and PGRL1 proteins together. A mutation that inactivates Arabidopsis PGR5 destabilises the protein in Synechocystis. Furthermore, the Synechocystis protein Sll1217, which exhibits weak sequence similarity with PGRL1, physically interacts with both plant and cyanobacterial PGR5 proteins, and stimulates CEF in Synechocystis. Therefore, Sll1217 partially acts as a PGRL1 analogue, the mode of action of PGR5 and PGRL1/Sll1217 proteins is similar in cyanobacteria and plants, and PGRL1 could have evolved from a cyanobacterial ancestor.